Livelihood contribution, problems and prospects of aquaculture inintegrated coastal farming systems - Ponnusamy, K; Gupta, Jancy (Indian Journal of Fisheries, 2016)
Integrating different enterprises for maximising farm productivity is the tradition of Indian farmers. Aquaculturein combination with other farm enterprises in the coastal regions of the country significantly contributes to thelivelihood security of farm families in a system's perspective. The review of previous studies showed thataquaculture significantly contributed for the generation of additional income and employment and resourceutilization in aquaculture based farming systems. However, high investment in the initial stage, encroachment ofvillage commons and marketing of different produces are some of the constraints to be addressed throughappropriate technological and policy interventions to make it more complimentary to the coastal farming systems.